Metode Dakwah Di Nusantara (Vernakulasi, Akulturasi, Asimilasi, Akomodasi) - Nur Fitriyani, Nur Fitriyani; Fauzia Nur Aeni, Fauzia Nur Aeni (Lembaga Sepercenter, 2024)
Indonesia, with its cultural and religious diversity, has a long history of the process of spreading Islam in a peaceful manner. The da'wah method used by the spreaders of Islam in the archipelago really respects local culture and applies a persuasive approach. This article examines the four main methods used, First Vernakulasi, which is the process of translating and disseminating Islamic teachings in local languages. This makes it easier for the local community to absorb Islamic values ​​more naturally. Second Acculturation is a process of mixing Islamic culture with local culture, so that a new, harmonious culture is formed. Third Assimilation involves unifying elements of Islam with local traditions without losing their respective identities. Fourth accommodation is adapting Islamic teachings to the local cultural context without sacrificing its main principles.This approach shows the flexibility and openness of Islam in adapting to cultural diversity, as well as respecting local wisdom. This article analyzes the implementation of these methods in the history of the spread of Islam in various regions of the archipelago, as well as their positive impact on the social and cultural life of society.